2015
DOI: 10.1093/restud/rdv023
|View full text |Cite
|
Sign up to set email alerts
|

College-Major Choice to College-Then-Major Choice

Abstract: Many countries use college-major-specific admissions policies that require a student to choose a college-major pair jointly. Given the potential of student-major mismatches, we explore the equilibrium effects of postponing student choice of major. We develop a sorting equilibrium model under the college-major-specific admissions regime, allowing for match uncertainty and peer effects. We estimate the model using Chilean data. We introduce the counterfactual regime as a Stackelberg game in which a social planne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 31 publications
(30 reference statements)
1
31
0
Order By: Relevance
“…The authors found that switching from a Chilean model to an open major choice system like the one that is in place in the United States would increase student welfare by one percent. This improvement in welfare was found to be even more pronounced for low income, low ability, and female students (Bordon and Fu, 2015).…”
Section: Comparisons Of Different Major Selection Systemsmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors found that switching from a Chilean model to an open major choice system like the one that is in place in the United States would increase student welfare by one percent. This improvement in welfare was found to be even more pronounced for low income, low ability, and female students (Bordon and Fu, 2015).…”
Section: Comparisons Of Different Major Selection Systemsmentioning
confidence: 90%
“…Students there apply to specific major and university combination. The ability to transfer between programs is so limited that most students that want to switch programs must drop out and reapply to start over in another desired major/university combination (Bordon and Fu, 2015). On the other hand, very permissive systems like the one at many universities in the United States only lightly restrict transfers between majors and allow students to apply undeclared and remain so until they find a major choice that they like.…”
Section: University Policiesmentioning
confidence: 99%
“…Students get enrolled only in the topmost program in which they got accepted. For a thorougher description of the Chilean higher education admission system, see Bordon and Fu (2015).…”
Section: Institutional Settingmentioning
confidence: 99%
“…The most important decision is the choice of a major. Arcidiacono () and Bordon and Fu () develop and estimate dynamic models of choice of academic major under uncertainty. Last, in Epple et al.…”
Section: Introductionmentioning
confidence: 99%
“…The most important decision is the choice of a major. Arcidiacono (2005) and Bordon and Fu (2015) develop and estimate dynamic models of choice of academic major under uncertainty. Last, in Epple et al (2017), we developed the basic theoretical model to examine effects of policy changes on attendance patterns and student costs.…”
Section: Introductionmentioning
confidence: 99%